2003
DOI: 10.1021/jo034632q
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Self-Assemblies of β-Cyclodextrins with Aromatic Tethers:  Factors Governing the Helical Columnar versus Linear Channel Superstructures

Abstract: A series of 6-O-(p-substituted phenyl)-modified beta-cyclodextrin derivatives, i.e., 6-O-(4-bromophenyl)-beta-CD (1), 6-O-(4-nitrophenyl)-beta-CD (2), 6-O-(4-formylphenyl)-beta-CD (3), 6-phenylselenyl-6-deoxy-beta-CD (4), and 6-O-(4-hydroxybenzoyl)-beta-CD (5), were synthesized, and their inclusion complexation behavior in aqueous solution and self-assembling behavior in the solid state were comparatively studied by NMR spectroscopy, microcalorimetry, crystallography, and scanning tunneling microscopy. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
41
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 62 publications
4
41
0
1
Order By: Relevance
“…In contrast, modified β-CDs 2 [11] and 3 [10] behave somewhat differently, forming the self-inclusion complexes in solution, the aromatic moiety of which is shallowly embedded in own β-CD cavity. Therefore, the difference of conformation in aqueous solution may be attributed to the diversity of pivot heteroatoms in 1-4.…”
Section: Self-assembly Behavior In Solutionmentioning
confidence: 97%
See 4 more Smart Citations
“…In contrast, modified β-CDs 2 [11] and 3 [10] behave somewhat differently, forming the self-inclusion complexes in solution, the aromatic moiety of which is shallowly embedded in own β-CD cavity. Therefore, the difference of conformation in aqueous solution may be attributed to the diversity of pivot heteroatoms in 1-4.…”
Section: Self-assembly Behavior In Solutionmentioning
confidence: 97%
“…We have recently reported systematical studies on the binding behaviors of mono-modified β-CDs both in solution and the solid state. The obtained results indicated that the assembly modes of polymeric supramolecules might be gov erned through the precise control of structures and chemical properties of substituents [10] . In the present study, we wish to report the self-assembly behavior of mono(6-phenolic-6-deoxy)-β-cyclodextrin (1) both in solution and the solid state by means of X-ray crystallography and 1 H NMR.…”
mentioning
confidence: 90%
See 3 more Smart Citations